Traduzione in lingua italiana e validazione del questionario standardizzato Nordic IRSST per la rilevazione di disturbi muscoloscheletrici / Italian translation and validation of the Nordic IRSST standardized questionnaire for the analysis of musculoskeletal symptoms - Gobba, F.; Ghersi, R.; Martinelli et al., S. (La Medicina del Lavoro, 2008)
Abbiamo sottoposto a traduzione in lingua italiana la versione del Nordic Muskuloskeletal Questionnaire (NMQ) proposta nel 2001 dall’IRSST canadese. lI NMQ è stato sottoposto alle procedure attualmente proposte per la traduzione e validazione di questionari in ambito sanitario. In particolare, la prima traduzione del questionario è stata retrotradotta da parte di traduttori indipendenti per verificare la rispondenza rispetto all’originale. In 40 lavoratori è stato quindi condotto un pre-test volto a valutare la comprensibilità del testo, che è risultata buona, la stabilità e la coerenza interna, anch’esse risultate complessivamente eccellenti o buone. In un ulteriore gruppo di 30 persone è stata valutata la sensibilità anamnestica, che si è dimostrata ottima. Infine la coerenza interna è stata ulteriormente confermata sul campo mediante una sperimentazione preliminare in 98 lavoratori addetti al montaggio in un’azienda metalmeccanica. Su queste basi si può concludere che la versione italiana del NMQ è appropriata per l’autosomministrazione, e può essere considerata affidabile per studi sul campo sui disturbi muscolo-scheletrici in gruppi di lavoratori e sulla percezione della disabilità correlata.Italian translation and validation of the Nordic IRSST standardized questionnaire for the analysis of musculoskeletal symptomsBackground: Data on self-reported symptoms and/or functional impairments are important in research on work-related musculoskeletal disorders (WRMSDs). In such cases the availability of international standardized questionnaires is extremely important since they permit comparison of studies performed in different Countries. Objectives: Translation into Italian and validation of the Nordic Musculoskeletal Questionnaire (NMQ), a tool which is widely used in studies on WRMSDs in the international scientific literature. Methods: The extended Canadian version of the NMQ was translated into Italian. As per the current guidelines, the crosscultural adaptation was performed by translation of the items from French, back-translation by independent mother-tongue translators and committee review. The resulting version of the questionnaire underwent pre-testing in 3 independent groups of subjects. The comprehensibility, reliability (internal consistency and reproducibility) and sensitivity were evaluated. Results: After translation/back-translation and review of the items the comprehensibility of the Italian version of the questionnaire was judged good in a group of 40 workers. The internal consistency was evaluated using the Cronbach’s Alpha test in the same group and in another 98 engineering workers: the results were on the whole acceptable.The reproducibility, which was tested with Cohen’s Kappa test in the 40 workers, was good/excellent. In a preliminary evaluation, performed in 30 outpatients of a of Rehabilitation Service, sensitivity was very good. Conclusions: The results show that the Italian version of the Nordic Musculoskeletal Questionnaire is valid for self-administration and can be applied in “field” studies on self-reported musculoskeletal symptoms and functional impairments in group of workers.